Implementation of the First In First Out Queue System by the Banyuwangi Police Traffic Unit - Muhammad Vito Romadhonsyah (Advances in Police Science Research Journal, 2021)
This research was motivated by the construction of a prototype Satpas by the Banyuwangi Police in June 2019 which included a First In First Out (FIFO) queue system to overcome various queuing problems in SIM services. However, some of these problems still occur. Therefore, a study was conducted that aims to determine the FIFO queuing system, the implementation of the FIFO queuing system, and determine the factors that influence the implementation of the FIFO queuing system in improving the quality of SIM services by the Banyuwangi Traffic Police. This study uses a qualitative approach with field research, as well as data collection techniques by interviewing, observing, and reviewing documents. The results of the study found that the implementation of the FIFO queuing system had met 14 components of service standards regarding public services. However, the FIFO queuing system is not fully utilized in the SIM service process. The system which should consist of two applications is only used one for the print queue application while the queue management application is turned off. The influencing factors consist of factors that support and factors that hinder the implementation of the FIFO queuing system. These two factors each have Personal Factors, Leadership Factors, Team Factors, System Factors, and Contextual / Situational Factors that support or hinder the implementation of the FIFO queuing system.